Seeking Liver Fibrosis in Biliary Atresia using De Ritis Ratio - Farahdina Farahdina; Rendi Aji Prihaningtyas; Bagus Setyoboedi; Agnescia Clarissa Sera; Sjamsul Arief (Biomolecular and Health Science Journal)
Introduction: Biliary atresia (BA) is a rare and devastating pediatric liver disorder characterized by progressive obstruction or absence of the extrahepatic bile ducts within infants. One crucial aspect of understanding the disease process is the assessment of liver fibrosis. The De Ritis ratio can serve as an early screening tool for clinicians that assists in identifying patients at risk of progressive fibrosis. Combining this ratio with other noninvasive markers and imaging techniques may further enhance its accuracy in assessing the severity of fibrosis. Our study aims to investigate the utility of the De Ritis (aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio and serum albumin levels as noninvasive markers of liver fibrosis in BA. Methods: This research was a cross-sectional study utilizing medical record data of pediatric patients with BA from November 1, 2022, to November 30, 2023. Sex, age, presence of malnutrition, and blood parameters including hemoglobin, leucocytes, and platelets (Plts) were collected. AST/ALT ratio and other laboratory parameters’ correlations were analyzed using Spearman’s correlation. Results: There was a positive correlation between the De Ritis ratio and Plts (P < 0.001, r = 1.000), activated partial thromboplastin time (P < 0.001, r = 1.000), partial thromboplastin time (P < 0.001, r = 0.999), and albumin (P < 0.001, r = 1.000). Conclusion: The De Ritis ratio and albumin levels have association with liver fibrosis formation might suggesting their potential use as predictive markers for disease progression in children with BA optimizing the patient’s nutritional well-being.